Vibrational properties of graphdiynes as 2D carbon materials beyond graphene. Issue 17 (20th April 2022) - Serafini, P.; Milani, A.; Tommasini, M.; Castiglioni, C.; Proserpio, D. M.; Bottani, C. E.; Casari, C. S.
Abstract : Raman and IR spectra investigation of 2D carbon crystals belonging to the family of graphdiynes (GDYs) and having different structures is performed in this paper, focusing on how these spectra are affected by different topological features. Abstract : Two-dimensional (2D) hybrid sp–sp 2 carbon systems are an appealing subject for science and technology. For these materials, topology and structure significantly affect electronic and vibrational properties. We investigate here by periodic density-functional theory (DFT) calculations the Raman and IR spectra of 2D carbon crystals belonging to the family of graphdiynes (GDYs) and having different structures and topologies. By joining DFT calculations with symmetry analysis, we assign the IR and Raman modes in the spectra of all the investigated systems. On this basis, we discuss how the modulation of the Raman and IR active bands depends on the different interactions between sp and sp 2 domains. The symmetry-based classification allows identifying the marker bands sensitive to the different peculiar topologies. These results show the effectiveness of vibrational spectroscopy for the characterization of new nanostructures, deepening the knowledge of the subtle interactions that take place in these 2D materials.